ChemInform Abstract: CaF2‐Catalyzed SN2‐type Chlorodehydroxylation of Chiral Secondary Alcohols with Thionyl Chloride: A Practical and Convenient Approach for the Preparation of Optically Active Chloroalkanes. Issue 32 (18th July 2013) - Zhang, Junjie; Wang, Huanxia; Ma, Yun; Wang, Youming; Zhou, Zhenghong; Tang, Chuchi
Abstract The SOCl2/CaF2 system shows superior properties compared to SOCl2/Py with regards to higher yields and enantioselectivity and is found to be suitable for large scale preparations.